Effect of silver content on the antibacterial and bioactive properties of silver‐substituted hydroxyapatite. Issue 9 (24th January 2013) - Lim, Poon Nian; Teo, Erin Yiling; Ho, Bow; Tay, Bee Yen; Thian, Eng San
Abstract : The long‐term success of a biomaterial used during surgery may be compromised by infection. A possible effective solution is to make the biomaterial osteoconductive and antibacterial. A range of silver‐substituted hydroxyapatite (AgHA) of up to 1.1 wt. % of Ag was synthesized. AgHA displayed a rod‐like morphology of dimensions ∼50 nm in length and ∼15 nm in width. Phase‐pure AgHA was demonstrated in the X‐ray diffraction patterns and Fourier transform infrared spectroscopy spectra. Comparing with hydroxyaptite (HA), 0.5AgHA exhibited a 3‐log reduction in the number of bacteria. Diffusion of the entrapped Ag + ions towards the crystal structure surface was revealed by an increase of 6 at. % Ag in the X‐ray photoelectron spectroscopy results. Furthermore, less than 0.5 ppm of Ag + ions being released from 0.5AgHA into the deionized water medium was evidenced from the inductively coupled plasma mass spectrometry results. AgHA produced by co‐precipitation gave rise to minimal release of Ag + ions. It was hypothesized that the diffused surface Ag + ions damaged the bacteria cell membrane and impede its replication. With the culturing time, significant increase in the number of human mesenchymal stem cells ( p < 0.05) was demonstrated on 0.5AgHA. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2456–2464, 2013.